COUNTER TERRORISM: AN ASSESSMENT OF MULTINATIONAL JOINT TASK FORCE (MNJTF) IN COMBATING BOKO HARAM INSURGENCY IN THE LAKE CHAD REGION - Ibekwe, Emmanuel Ogueri; Nosiri, Uzoma D. (African Journal of Social and Behavioural Sciences, 2023)
The devastating impact of terrorism (Boko Haram) in the Lake Chad region had led to several counter terrorism measures among states within the region. One of the key measures is the setting up of a Multinational Joint Task Force (MNJTF) for ease of cooperation and collaboration against this common enemy. This paper seemed to assess the operations of this Multinational Joint Task Force (MNJTF) so far. Specifically, the paper aimed to evaluate the role of MNJTF in combating Boko Haram insurgency; identify the challenges of MNJTF towards combating the operation of Boko Haram insurgency and proffer solutions on how to effectively tackle the spread and operations of the insurgents. The regional security complex theory was adopted as framework for analysis. The documentary method as secondary source was adopted to gather data and content and logic reasoning were used for analysing the data. It was discovered that the MNJTF had helped to stifle the operations of Boko Haram insurgents within the region which is evident in the reported number of recaptured territories, downgrading of the terrorists’ capability, freeing of abductees, facilitation of return of IDPs and refugees and facilitation of humanitarian assistance. However, it is faced with the challenge of further dismantling the grip of the insurgents in more locations in the region, as they keep changing their operational strategies to avoid detection by security operatives. Secondly, it was revealed that trust issue; challenge of finance, problem of effective collaboration and cooperation, human right challenge, poor border security, limited police capability and inadequate military equipment are some of the notable challenges to the effective operation of the MNJTF. The paper recommended deepened collaboration, building or development of police capability or component, rejig of current border security strategies in place within the region, enhanced funding, adequate and sustainable training, elicit stronger support from international organizations, intelligent gathering etc.